Implementasi Fungsi Manajemen dalam Kegiatan Bimbingan Pre-Marital Health di Klinik Nikah (KLIK) Medan - Rahmi, Ade Laili; Soiman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This article discusses the application of management functions in pre-marital health guidance activities at the Medan Marriage Clinic. In good management there is a management function to achieve the expected goals of an institution. This research was motivated by a lack of health education from prospective partners or husband and wife in navigating a household using Islamic law and the couple was not prepared mentally and scientifically regarding marriage and the rights and obligations in running a household. Medan Marriage Clinic is a program that helps people with pre-marital and post-marital matters. One of the activities is about pre-marital health guidance which discusses the importance of health before marriage. Islam is closely related to health, because it has the same goal, namely for the good of humans. In this research the author used a qualitative method, namely by using interview, observation and documentation techniques. The results of the research show that pre-marital health guidance activities at the Medan Marriage Clinic implement management functions starting from carrying out plans in arranging activity schedules, organizing in accordance with each division, implementation of activities has been fulfilled thereby increasing understanding of the importance pre-marital health, as well as coaching carried out with supervision of the division to find out whether activities are running well or whether there are deficiencies in the program that has been implemented.